35.3k views
5 votes
Factor completely 3x2+2x-1

User Dreampie
by
5.3k points

2 Answers

6 votes

Answer:

x = 1/3 or x = -1

Explanation:

3x^2 + 2x - 1

=> 3x^2 + 3x - 1x - 1 product = -3 sum = 2

=> 3x( x + 1 ) - 1(x + 1 )

=> (3x - 1) (x + 1)

3x = 1

=>x=1/3 or x = -1

HOPE THIS HELPS YOU ~

User Onlineracoon
by
5.5k points
6 votes

Answer:

(x + 1) (3x - 1)

Explanation:

Using the AC method, here a = 3, b = 2, and c = -1.

ac = 3 * -1 = -3

Factors of -3 that add up to +2 are +3 and -1.

Divide by a: +3/3, -1/3

Reduce: +1/1, -1/3

So the factors are x + 1 and 3x - 1.

3x² + 2x - 1 = (x + 1) (3x - 1)

User Vtolentino
by
4.9k points